Recent advances in traffic signal performance evaluation - Dallas Leitner; Piro Meleby; Lei Miao (Journal of Traffic and Transportation Engineering (English ed. Online), 2022)
Signal retiming is a prominent way that transportation agencies use to fight congestion and change of traffic pattern. Performance evaluations of traffic conditions at signalized intersections and arterials provide actionable data for agencies to make well-informed and prioritized signal retiming decisions. However, the abundance of data sources, the lack of standardized evaluation methods and oftentimes the shortage of resources make it a difficult endeavor. The review detailed in this paper examines the advances made in traffic signal performance evaluation. We establish the necessity for the evaluations, study the process of continuous improvement of traffic signal performance using the evaluations, and then examine multiple methodologies in a plethora of research endeavors. Particularly, we focus on probe vehicles and sensors data, the two major sources of data. We discuss how sensors are connected to signal controllers to provide relevant in-depth traffic data including speed and occupancy measures. We also review the nature of probe vehicles and the level of penetration. We then define and summarize performance measures derived from both sources, to aid in performance evaluations. For performance evaluation methods, we discuss the research studies and provide summaries including advantages and disadvantages of the methods used, as well as a holistic outlook for future research. This paper is aimed to provide a comprehensive review on the state-of-the-art to benefit researcher, traffic agencies, and commercial entities that thrive to improve safety and efficiency of traffic signals through performance evaluations.